SPECIFIC FEATURES OF DEVELOPING HIGH MORAL AND SPIRITUAL EDUCATION IN YOUTH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
We can include the following as factors that shape the moral behaviour of young people: reading books, being raised in a spirit of respect for our national values, diligently studying the priceless historical heritage left by our great scholars, learning the folk oral traditions, and similar influences.